Linking biodiversity indicators, ecosystem functioning, provision ofservices and human well-being in estuarine systems: Application of aconceptual framework - Pinto, Rute (2014)
Assuming that human well-being strongly relies on the services provided by well-functioning ecosys-tems, changes in the ecological functioning of any system can have direct and indirect effects on humanwelfare. Intensive land use and tourism have expanded in recent decades along coastal ecosystems,together with increasing demands for water, food and energy; all of these factors intensify the exploita-tion of natural resources. Many of the interrelations between ecosystem functioning and the provisionof ecosystem services (ES) still require quantification in estuarine systems. A conceptual framework toassess such links in a spatially and temporally explicit manner is proposed and applied to the Mondegoestuary (Portugal). This framework relies on three consecutive steps and discriminates among biodi-versity structural components, ecosystem functioning and stability and the services provided by theecosystem.Disturbances in abiotic factors were found to have a direct effect on biodiversity, ecosystem functioningand the provision of ES. The observed changes in the species composition of communities had a positiveeffect on the ecosystem’s productivity and stability. Moreover, the observed changes in the estuarineES provision are likely to arise from changing structural and abiotic factors and in the present casefrom the loss or decline of locally abundant species. This study also indicates that linear relationshipsbetween biodiversity, ecosystem functioning and services provision are unlikely to occur in estuarinesystems. Instead, cumulative and complex relations are observed between factors on both temporaland spatial scales. In this context, the results suggest several additional conclusions: (1) biodiversityand ecosystem functioning interaction with human well-being need to be incorporated into decision-making processes aimed at the conservative management of systems; (2) the institutional use of researchresults must be part of the design and implementation of sustainable management activities; and (3)more integrative tools/studies are required to account for the interactions of estuarine ecosystems withsurrounding socio-economic activities. Therefore, when performing integrated assessments of ecosystemdynamics, it becomes essential to consider not only the effects of biodiversity and ecosystem functioningon services provision but also the effects that human well-being and ES provision may have on estuarinebiodiversity and ecosystem functioning.The proposed framework implies taking into account both the functional and the commoditiespoints of view upon natural ecosystems and by this representing a line of thought which will deservefurther research to explore more in detail the conceptual links between biodiversity–ecosystemfunctioning–services provided.